Analysis of the Decision of the Bogor Religious Court on the Causes of Divorce of Husband and Wife Due to Online Gambling. - rahmayanti, putri; Hambari,; Rusdi Kasman,; Zuhratun Nakhwah, (MIZAN: JOURNAL OF ISLAMIC LAW, 2025)
This study discusses the causes of divorce due to online gambling and how the opinion of the Bogor Religious Court judge in deciding Case Number 1273/Pdt.G/PA.Bgr. The method used in this research is qualitative method The type of research conducted by researchers is using library research, namely research by trying to analyze, explain and describe the latest facts and find correlations between one another. The fact that is the object of this research is the decision of the Bogor Religious Court judge with Case Number 1273/Pdt.G/2024/PA.Bgr so that in solving it data collection must be carried out using rules, theories, arguments and so on so that the results are in line with the issues that the author conveys. The results of this study indicate that the causes of divorce due to online gambling can affect a relationship in marriage, including the effects of addiction to online gambling games which cause the husband to be unable to meet the needs of his family and cause conflict that ends in divorce. The reasons raised by the Defendant (wife) are in line with Article 19 of Government Regulation Law (PP) Number 9 of 1975 letters a and letter f and article 116 of the Compilation of Islamic Law (KHI) letters a and letter f. Factors The judge's consideration efforts carried out subjectively and objectively by religion to prevent divorce, regarding divorce cases due to online gambling and factors causing online gambling. Keywords: Religious Court Decisions, Divorce, Online Gambling